2021
DOI: 10.3390/nano11030615
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Proteins Regulated during Cadmium Sulfide Quantum Dots Response in Arabidopsis thaliana Wild Type and Tolerant Mutants

Abstract: In previous work, two independent Arabidopsis thaliana Ac/Ds transposon insertional mutant lines, atnp01 and atnp02, were identified that showed a higher level of tolerance than the wild type (wt) line to cadmium sulfide quantum dots (CdS QDs). The tolerance response was characterized at physiological, genetic and transcriptomic levels. In this work, a comparative analysis was performed on protein extracts from plantlets of the two mutants and of wt, each treated with 80 mg L-1 CdS QDs. A comparative protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 87 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…With regard to CdS QDs and CdSO 4 , the negative effects on biomass and other physiological parameters were also consistent with previous studies , as with a strong decrease in photosynthetic activity, cellular respiration, and ROS scavenging, as a consequence of disrupted organellar functions with increasing exposure time and CdS QD concentration . It has been demonstrated that CdS QDs and CdSO 4 trigger different regulatory responses at the level of mRNA and proteins. ,,,, Concerning the effects observed for ZnS QDs, the literature related to this pristine type of QD is minimal. However, information related to ZnO NPs effects on plant species is abundant, and mostly in agreement with the results reported in Ruotolo et al: decreased chlorophyll production and induction of secondary metabolite biosynthesis.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…With regard to CdS QDs and CdSO 4 , the negative effects on biomass and other physiological parameters were also consistent with previous studies , as with a strong decrease in photosynthetic activity, cellular respiration, and ROS scavenging, as a consequence of disrupted organellar functions with increasing exposure time and CdS QD concentration . It has been demonstrated that CdS QDs and CdSO 4 trigger different regulatory responses at the level of mRNA and proteins. ,,,, Concerning the effects observed for ZnS QDs, the literature related to this pristine type of QD is minimal. However, information related to ZnO NPs effects on plant species is abundant, and mostly in agreement with the results reported in Ruotolo et al: decreased chlorophyll production and induction of secondary metabolite biosynthesis.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, for CdS QDs, Marmiroli et al recently demonstrated that nanoparticle biotransformation occurs within the plant cell, resulting in a chemical form different from ionic Cd. This distinction between ionic and nanoscale form has also been demonstrated through specific transcriptomic responses to CdS QDs and Cd 2+ exposure, , and by a nanoscale specific proteomic response . The second component ( x axis; Figure a) is related to the ptDNA and mtDNA copy number; these treatments trigger a copy number increase (Fe 3 O 4 NPs, FeCl 3 , ZnS QDs, ZnSO 4 ) from those that had no effect (CeCl 3 , CeO 2 NPs, Fe 2 O 3 NPs) or those that had a nonuniform impact on ptDNA and mtDNA (CdS QDs, CdSO 4 ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As explained in one of the reviews included in this Special Issue, the number and quantity of nanomaterials is ever increasing and affecting the environment where humans, bacteria, and plants live, and their genome come in contact with nanomaterials [3]. Although the topic of genotoxicity induced by nanomaterials is important, we had only five contributions for this Special Issue: [3][4][5][6][7][8]. Marmiroli et al, 2022 [3], contributed a minireview on the methods used to analyze genotoxicity in plants.…”
mentioning
confidence: 99%